Approaching listening and speaking skills using online to facilitate interactive learning from students' perspectives / Puteri Rohani Megat Abdul Rahim ... [et al.] - Megat Abdul Rahim, Puteri Rohani; Idris, Sheema Liza; Abdul Rahman, Zarinatun Ilyani; Ya Shaq, Mohamed Syafiq; Nasir, Nur Farhana (Universiti Teknologi MARA, 2021)
Teaching and learning process is constantly transforming due to the ever-increasing globalization. In the educational sector the use of information and communication technology (ICT) is constantly changing due to the increasing trend in globalization. This has resulted in the change and transformation the facet of education in this 21st century. The various usage of technologies and other forms of learning materials that have been extensively used has created a medium where students able to be interactive because it is learner centred, and the environment of online learning is more open and flexible. However, several studies showed that students prefer traditional classroom more because they would prefer face-to-face communication with their instructor. Thus, this study intends to explore the perspective of learning listening and speaking using online among L2 learners. A total number of 102 university students at UiTM Perak Branch took part in this study. They were instructed to answer a set of questionnaires which was created using google document. From the findings the students reported that they do see the benefits of online learning. In addition, they found learning through this interactive medium as interesting and provide them space to progress at their own pace in learning. However, this does not portray students' eagerness in which may be due to several factors. This study is hoped to able to highlight the positive aspects of using online as an alternative to the traditional way of teaching listening and speaking.